Emerging Roles of T Helper Cells in Non-Infectious Neuroinflammation: Savior or Sinner - Liu, Wenbin; Fan, Meiyang; Lu, Wen; Zhu, Wenhua; Meng, Liesu; Lu, Shemin (Frontiers in Immunology, 2022)
CD4+ T cells, also known as T helper (Th) cells, contribute to the adaptive immunity both in the periphery and in the central nervous system (CNS). At least seven subsets of Th cells along with their signature cytokines have been identified nowadays. Neuroinflammation denotes the brain’s immune response to inflammatory conditions. In recent years, various CNS disorders have been related to the dysregulation of adaptive immunity, especially the process concerning Th cells and their cytokines. However, as the functions of Th cells are being discovered, it’s also found that their roles in different neuroinflammatory conditions, or even the participation of a specific Th subset in one CNS disorder may differ, and sometimes contrast. Based on those recent and contradictory evidence, the conflicting roles of Th cells in multiple sclerosis, Alzheimer’s disease, Parkinson’s disease, epilepsy, traumatic brain injury as well as some typical mental disorders will be reviewed herein. Research progress, limitations and novel approaches concerning different neuroinflammatory conditions will also be mentioned and compared.